"Life behind the mask": Sexual life of Iranian women with multiple sclerosis. Issue 2 (April 2018) - Dehghan-Nayeri, Nahid; Khakbazan, Zohreh; Ghafoori, Faezeh
Abstract: Background: Multiple sclerosis (MS) is a debilitating and life-long disease that affects the sexual life of people. However, in Iran little attention has been paid to the sexual life of women with MS. Objective: The aim of this study was to understand the sexual life and experiences of Iranian women with multiple sclerosis. Methods: A qualitative study was designed, and face-to-face semi-structured interviews were conducted with twenty-five women with MS. The interviews were tape-recorded and transcribed verbatim. Data were analyzed using a content analysis approach and through MAXQDA.10 software. Results: The main themes identified during the analysis were: (1) limited sexual activity, (2) sex life behind the mask, and (3) lack of sexual support during the rehabilitation process. In fact, the participants in this study expressed that their sexual activity was negatively affected by MS. They were trying to hide their sexual problems, and present themselves to their husbands differently from what they are, which can be considered as sex life behind the mask. Furthermore, Iranian women with MS received little sexual support from the rehabilitation team. Conclusions: Hiding sexual problems from husbands is thought to be a common practice and behavior among Iranian women with MS. Understanding this insight and its consequences can assist the rehabilitation team in helping and solving sexual problems of women with MS. Moreover, sexual awareness and education should be extended, especially among the husbands of women with MS.